The Relationship between Social Irresponsibility and Deviant Behavior in the Workplace: The Mediating Role of Moral Anger - Najme Jalalian; Aref Dowlat (International Journal of Ethics and Society)
Introduction: Social responsibility as an ethical framework commits a person, whether an individual or an organization, to participate in social affairs, the implementation of which will benefit society at large. Given the importance of this component, the aim of this study is to investigate the relationship between social irresponsibility and deviant behavior in the workplace with regard to the mediating role of moral anger in employees of Yasuj University of Medical Sciences. Material and Methods: The research method is of an applied type based on the purpose and is descriptive-survey in nature. The statistical population of this study is 141 employees of Yasuj University of Medical Sciences, which was selected as a sample due to the small size of the target population. The data collection tools were questionnaires on social irresponsibility, deviant behavior, and moral anger. Descriptive statistics and inferential statistics (structural equation modeling method with partial least squares approach) in SPSS and PLS software were used to analyze the data. Results: The results of the findings showed that social irresponsibility has a positive and significant effect on moral anger, moral anger has a significant and positive effect on deviant behavior, social irresponsibility has a significant and positive effect on deviant behavior, and social irresponsibility has a significant and positive effect on deviant behavior, considering the mediating role of moral anger. Conclusion: The complex relationships between the research variables indicate that the higher the anger and moral deviance in individuals, the greater the likelihood of aggressive behavior and social irresponsibility.